The concrete blonde - Connelly, Michael (New York : Warner Books, 2007)
The family of a notorious serial killer whom homicide detective Harry Bosch shot during an arrest four years ago has accused him of killing the wrong man, and has filed a civil suit against the LAPD. The allegation becomes horrifyingly plausible when a new murder occurs with all the hallmarks of the dead slayer's style.
National College of Business and Arts
Keywords: Serial murders -- Fiction; Detective and mystery fiction